Assessing vocabulary - Read, John A. S (Cambridge University Press, 2011)
Series editors' preface -- Acknowledgements -- 1. The place of vocabulary in language assessment -- 2. The nature of vocabulary -- 3. Research on vocabulary acquisition and use -- 4. Research on vocabulary assessment -- 5. The design of discrete vocabulary tests -- 7. Comprehensive measures of vocabulary -- 8. Further developments in vocabulary assessment -- References -- Index; First published 2000; Includes bibliographical references and index